The effect of the SARS-CoV-2 pandemic on suspected cancer referrals at a regional head and neck unit - Andrew Hannah; Terry Lowe (Elsevier, 2022)
The novel coronavirus SARS-CoV-2, initially identified in late 2019 as a small case cluster, has rapidly become a global pandemic. Government restrictions, closure of primary care services, interruption of cancer screening programmes, and fear of contracting the virus have demonstrably led to a reduction in referrals for suspected cancer and delays to treatment across the United Kingdom. A retrospective analysis was carried out on suspected cancer referrals to the maxillofacial service at Aberdeen Royal Infirmary during the 12 months from March 2020, and compared with the 12 months prior. Suspected cancer referrals reduced by 38.6% (p < 0.001) during this period, with a reduction in the percentage referred by General Dental Practitioners. Further analysis shows a proportionate reduction in squamous cell carcinoma diagnoses, with other diagnoses remaining stable. Time from referral to first appointment, biopsy, and treatment showed no change. Stage at diagnosis and treatment modality was also unaffected. Assuming no change to the incidence of head and neck malignancies, over a third of new malignancies may have been undiagnosed during the 12 months from March 2020. Evidence for the impact of the pandemic is likely to become apparent as services return to pre-pandemic levels and these patients begin to present.